Surgical Practice in Girls with Congenital Adrenal Hyperplasia: An International Registry Study - GÜRAN, TÜLAY (KARGER, 2021)
In this article international trends in surgical practice in girls with congenital adrenal hyperplasia (CAH) are evaluated. All cases that had been classified in the I-CAH/I-DSD registry as 46,XX CAH and who were born prior to 2017 were identified. Centers were approached to obtain information on surgical decision making. Of the 330 included participants, 208 (63.0%) presented within the first month of life, and 326 (98.8%) cases were assigned female. Genital surgery had been performed in 250 (75.8%). A total of 64.3, 89.2, and 96.8% of cases residing in Europe, South America and Asia, respectively, had at least one surgery. In a logistic regression model for the probability of surgery before the second birthday (early surgery) over time an increase of probability for early vaginal surgery could be identified, but not for clitoral surgery or both surgeries combined. Genitoplasty in girls with CAH remains controversial. This large international study provides a snapshot of current practice and reveals geographical and temporal differences. Fewer surgeries were reported for Europe, and there seems to be a significant trend towards aiming for vaginal surgery within the first 2 years of life.
Keywords: Congenital adrenal hyperplasia; Disorders of sexual development; Intersex; Surgery; 21-HYDROXYLASE DEFICIENCY; ENDOCRINE-SOCIETY; DISORDERS; SURGERY